Reusable elastomeric respirators in health care : considerations for routine and surge use - Liverman, Catharyn T.; Yost, Olivia C.; Rogers, Bonnie; Clever, Linda Hawes (National Academies Press, 2019)
Protecting the health and safety of health care workers is vital to the health of each of us. Preparing for and responding to a future influenza pandemic or to a sustained outbreak of an airborne transmissible disease requires a high-level commitment to respiratory protection for health care workers across the wide range of settings in which they work and the jobs that they perform. Keeping health care workers healthy is an ethical commitment both in terms of addressing the occupational risks faced by health care workers and of providing for the continuity of patient care and services needed to maintain the health of individuals and communities. During a public health emergency, challenges will arise concerning the availability of respiratory protective devices (i.e., respirators). Reusable respirators (specifically, reusable half-facepiece elastomeric respirators) are the standard respiratory protection device used in many industries, and they provide an option for use in health care that has to date not been fully explored. The durability and reusability of elastomeric respirators make them desirable for stockpiling for emergencies, where the need for large volumes of respirators can be anticipated. However, they are used infrequently in health care. Reusable Elastomeric Respirators in Health Care explores the potential for the use of elastomeric respirators in the U.S. health care system with a focus on the economic, policy, and implementation challenges and opportunities. This report examines the practicability of elastomeric use in health care on a routine basis and during an influenza pandemic or other large aerosol-transmissible outbreak, when demand for respiratory protective devices by U.S. health care personnel may be larger than domestic supplies. The report also addresses the issues regarding emergency stockpile management of elastomeric respiratory protective devices.
Keywords: Respirators (Medical equipment); Medical personnel -- Health and hygiene.; Medical personnel.; Emergency management.; Elastomers.; Ventilators, Mechanical; Health Personnel; Disaster Planning; Elastomers; United States; Health Workforce; Health Occupations; Respirateurs (Équipement médical); Personnel médical -- Santé et hygiène.; Personnel médical.; Gestion des situations d'urgence.; Élastomères.; disaster planning.; elastomer.; MEDICAL -- Pharmacology.; Medical personnel; Emergency management; Medical personnel -- Health and hygiene; Electronic books.